Clinical Practice Guidelines for the Nursing Management of Percutaneous Endoscopic Gastrostomy and Jejunostomy (PEG/PEJ) in Adult Patients: An Executive Summary. Issue 4 (July 2018) - Roveron, Gabriele; Antonini, Mario; Barbierato, Maria; Calandrino, Vita; Canese, Giancarlo; Chiurazzi, Lucio Fernando; Coniglio, Gesualdo; Gentini, Gabriele; Marchetti, Mara; Minucci, Andrea; Nembrini, Laura; Neri, Vanessa; et al.
Abstract : Enteral nutrition (EN) is the introduction of nutrients into the gastrointestinal tract through a tube placed in a natural or artificial stoma. Tubes may be passed into the stomach (gastrostomy) or the jejunum (jejunostomy) in patients who cannot obtain adequate nourishing via oral feeding. Following placement, nurses are typically responsible for management of gastrostomy or other enteral tube devices in both the acute and home care settings. This article summarizes guidelines developed for nursing management of percutaneous endoscopic gastrostomy or jejunostomy (PEG/PEJ) and gastrojejunostomy (PEGJ) tubes, developed by the Italian Association of Stoma care Nurses (AIOSS—Associazione Italiana Operatori Sanitari di Stomaterapia) in collaboration with the Italian Association of Endoscopic Operators (ANOTE—Associazione Nazionale Operatori Tecniche Endoscopiche) and the Italian Association of Gastroenterology Nurses and Associates (ANIGEA—Associazione Nazionale Infermieri di Gastroenterologia e Associati). The guidelines do not contain recommendations about EN through nasogastric tubes, indications for PEG/PEJ/PEGJ positioning, composition of EN, selection of patients, type of tube, modality of administration of the EN, and gastrointestinal complications Abstract : The CE test for this article is available online only at the journal website, jwocnonline.com, and the test can be taken online at NursingCenter.com/CE/JWOCN.